Peculiarity of structural and microstructural changes in the thymus in «catabolic» phase after experimental hyperthermia - S. V. Michurina; D. V. Vasendin; I. Yu Ischenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2013)
The aim of the research was to study the thymus cellular composition in 45 Vistar rats after experimental hyperthermia (EH). The animals were heated only once to thermoplegia. At different periods of the experiment (5 hours, 3 days after EH) the animals were killed under light narcosis then the thymus was excised for further study. Histologic specimens were prepared according to the basic methods. Immunoblasts, middle-size and small lymphocytes, cells with the mitosis shapes, epithelial cells, and macrophages (1000 magnification) were differentiated in all zones of the thymus on the standard area of 4500 mkm 2. Experimental hyperthermia was found to lead to accidental involution of the thymus. Involution of this organ corresponded to the «catabolic» phase of the posthyperthermal period (5 hours, 3 days after EH) that was expressed in the decrease of the relative weight of the organ (25 %), reduction of the relative area of the cortex (15 %) and density of the lymphocytes (12 %). Strengthening of the destructive processes, sings of perivascular oedema and migration of the cellular elements into lymphatic spaces and capillaries were found at the tissue level.